Agriculture's role in the Indian enigma: Help or hindrance to the undernutrition crisis? - Headey, Derek D.; Chiu, Alice; Kadiyala, Suneetha (International Food Policy Research Institute, 2011)
In recent decades India has achieved one of the fastest economic growth rates in the world, yet its progress against both child and adult undernutrition has been sluggish at best. While this Indian variant of the so-called Asian enigma presents many puzzles, one of the puzzles pertains to agriculture's role. In this paper we reassess agriculture's role in the Indian enigma by exploring two key pathways, an income-consumption pathway and an employment-time use pathway, linking agricultural conditions to nutrition outcomes. On the income-consumption front, we assess whether rising incomes are improving diets and how agriculture and income growth are influencing the Indian diet. In terms of time use, we explore whether agricultural livelihoods hinder childcare practices and the health status of mothers. We conclude with a brief overview of nonagricultural constraints to improved nutrition and some analysis of the implications of our findings for agricultural policies in India.